Multifunctional La10Si6O27:Tb3+ tailored material for photoluminescence, photocatalysis and electrochemical sensing applications - A. Naveen kumar; Ramachandra Naik; V. Revathi; H.C. Ananda Murthy; H.P. Nagaswarupa; C.R. Ravikumar; G.V. Ashok Reddy; Ramyakrishna Pothu; Rajender Boddula; H.B. Lokesh; Vijaya Shanbhag (Applied Surface Science Advances, 2023)
La10Si6O27: Tb3+ (1–9 mol%) materials were synthesized by the combustion method and characterized by PXRD, PL, CV, EIS and UV–Vis spectroscopy to explore its photoluminescent, electrochemical and photocatalytic properties. These materials exhibited crystalline and single phases even after doping Tb3+ ions into the lattice of La10Si6O27. PL analysis confirms a tunable and maximum emission for optimized concentration. Electrochemical analysis shows La10Si6O27:Tb3+ (9 mol%) electrode as a paracetamol and penegra sensing material. The average specific capacitance of this electrode at 10 mVs−1 was found to be 262 Fg−1. A Photocatalysis study was performed using La10Si6O27:Tb3+ (5 mol%) material as a photocatalyst for the degradation of direct green dyes. Therefore, La10Si6O27:Tb3+ can be used as a multifunctional material for photoluminescence, photocatalysis, and electrochemical sensing applications.